Transcriptional regulation of LGALS9 by HAND2 and FOXO1 in human endometrial stromal cells in women with regular cycles. (28th September 2021) - Murata, Hiromi; Tanaka, Susumu; Hisamatsu, Yoji; Tsubokura, Hiroaki; Hashimoto, Yoshiko; Kitada, Masaaki; Okada, Hidetaka
Abstract: Uterine natural killer cells are regulated via surface inhibitory receptors for IL15 and galectin-9 (LGALS9) secreted by endometrial stromal cells (ESCs). However, the mechanism that regulates LGALS9 mRNA levels in ESCs is unclear. The aim of this study is to clarify the transcriptional regulation of LGALS9 in ESCs. Here, LGALS9 mRNA expression levels significantly decreased in the endometrial tissue in the early- to mid-secretory phase, and recovered in the mid- to late-secretory phase, compared to that in the proliferative phase. In ESCs, LGALS9 mRNA expression significantly decreased following estradiol + medroxyprogesterone acetate treatment for 1 day and increased after 12 days compared to that in the control. The transcriptional activity of the LGALS9 upstream region was upregulated by heart and neural crest derivatives expressed 2 (HAND2) and downregulated by forkhead box O1 (FOXO1). In ESCs, HAND2 expression significantly increased throughout the 12 days treatment with steroid hormones, whereas FOXO1 expression significantly increased on Day 1, reached a plateau, and significantly increased again after 6 days of treatment. Levels of FOXO1 phosphorylation (pFOXO1) remained unchanged after a 3-day treatment of ESCs with steroid hormones, but significantly increased following a 12-day treatment. pFOXO1 could not bind to the DNA and was thus unable to directly suppress LGALS9 transcription. Therefore, expression level of HAND2 and phosphorylation status of FOXO1 may determine LGALS9 mRNA expression. This study provides a novel molecular mechanism underlying the transcriptional regulation of LGALS9 mRNA in ESCs, which could be valuable in the treatment of diseases associated with decidualization failure.